2017
DOI: 10.1016/j.clinph.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The associative brain at work: Evidence from paired associative stimulation studies in humans

Abstract: The original protocol of Paired Associative Stimulation (PAS) in humans implies repetitive cortical and peripheral nerve stimuli, delivered at specific inter-stimulus intervals, able to elicit non-invasively long-term potentiation (LTP)- and long-term depression (LTD)-like plasticity in the human motor cortex. PAS has been designed to drive cortical LTP/LTD according to the Hebbian rule of associative plasticity. Over the last two decades, a growing number of researchers have increasingly used the PAS techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
135
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 257 publications
(131 reference statements)
6
135
0
1
Order By: Relevance
“…[39][40][41] The PAS paradigm is based on the principle that was found in basic animal research of spike-timingdependent plasticity 118,119 ; specifically, it is a synaptic plasticity mechanism in which synaptic transmission is facilitated when presynaptic input precedes postsynaptic excitation (e.g., ISI of 21.5-25 ms), and transmission is inhibited when postsynaptic excitation precedes presynaptic input (e.g., ISI:~10 ms). [39][40][41] Huber et al examined the association between cortical plasticity as indexed by PAS using ISI of 25 or 10 ms and slow-wave sleep activity that is assumed to be associated with sleep need. They showed that PAS at an ISI of 25 ms led to long-term potentiation (LTP)-like changes in MEP and TEP, while PAS at ISI of 10 ms resulted in long-term depression (LTD)-like changes in MEP and TEP in areas both ipsilateral and contralateral to the stimulation site.…”
Section: Cortical Plasticity Indexed By Tep Pasmentioning
confidence: 99%
See 2 more Smart Citations
“…[39][40][41] The PAS paradigm is based on the principle that was found in basic animal research of spike-timingdependent plasticity 118,119 ; specifically, it is a synaptic plasticity mechanism in which synaptic transmission is facilitated when presynaptic input precedes postsynaptic excitation (e.g., ISI of 21.5-25 ms), and transmission is inhibited when postsynaptic excitation precedes presynaptic input (e.g., ISI:~10 ms). [39][40][41] Huber et al examined the association between cortical plasticity as indexed by PAS using ISI of 25 or 10 ms and slow-wave sleep activity that is assumed to be associated with sleep need. They showed that PAS at an ISI of 25 ms led to long-term potentiation (LTP)-like changes in MEP and TEP, while PAS at ISI of 10 ms resulted in long-term depression (LTD)-like changes in MEP and TEP in areas both ipsilateral and contralateral to the stimulation site.…”
Section: Cortical Plasticity Indexed By Tep Pasmentioning
confidence: 99%
“…This paradigm is called 'paired associative stimulation' (PAS), which is thought to be related to cortical plasticity at the stimulation site. [39][40][41] While there have been many TMS-EMG studies targeting M1, TMS-EEG research that extends TMS neurophysiology to the dorsolateral prefrontal cortex (DLPFC) has gradually been implemented. [42][43][44][45][46] Thus, there are several review articles for TMS-EMG for M1, 47,48 but only a few review papers summarizing TMS-EEG research for the non-motor areas, such as the DLPFC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a number of modified PAS protocols have been designed and tested in humans such as protocols able to promote plasticity in the spinal cord (Suppa et al . ). Spinal PAS might be in theory applied to harness plasticity for motor recovery in patients with various neurological disorders.…”
mentioning
confidence: 97%
“…The original PAS protocol described in humans (Stefan et al 2000) consists of repetitive cortical and peripheral nerve stimuli delivered at specific interstimulus intervals (ISIs), able to elicit long-term potentiation (LTP)-and depression (LTD)like plasticity in the primary motor cortex (M1). More recently, a number of modified PAS protocols have been designed and tested in humans such as protocols able to promote plasticity in the spinal cord (Suppa et al 2017). Spinal PAS might be in theory applied to harness plasticity for motor recovery in patients with various neurological disorders.…”
mentioning
confidence: 99%